PROTICTIVE EFFECTS OF VITAMINE E AGAINST TESTICULAR ENZYMES TOXICITY INDUCED BY CYPERMETHRIN IN MICE - TURKI M. AL SHAIKH; REFAAT IBRAHIM ELFAYOUMI (International Journal of Pharma and Bio Sciences, 2013)
Cypermethrin is a synthetic pyrethroid insecticide. It is known for its wide toxic manifestations. The present work was designed to evaluate the protective role of vitamin E on Cypermethrin intoxication in mice after 14 days. The weight of testis and activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), acid phosphatase (AcP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH were studied. Male mice were divided into four groups <s>of</s> 10 each: group I served as control and treated with corn oil; group II received cypermethrin (2.8 mg/kg BW) in corn oil. Group III received vitamin E (100 mg/kg BW) ;group IV received both cypermethrin and vitamin E (100 mg/kg BW) the animals were fed by feeding tube through the mouth. The data showed that the exposure of mice to cypermethrin caused a significant decrease in weight of testis and the activities of marker enzymes (AST), (ALT), (AcP) and (ALP) and a significant increase in LDH activity.Co-administration of vitamin E(100 mg/kg BW) to the cypermethrin group restored all the parameters cited above to near the control values. Therefore, this study revealed that vitamin E have beneficial effects against cypermethrin-induced toxicity.